Synthesis of New Derivatives of Cephalexin with Isatin and Glycine Schiff Bases - Shayma l. Abdulhadi (Journal of Global Pharma Technology, 2019)
Objectives: Two derivatives of cephalexin were synthesized by reaction with isatin-glycine Schiff base and bromoisatin-glycine Schiff base separately. Methods: Cephalexin was linked through the amine group to isatin glycine and bromoisatin glycine Schiff bases by amide bond formation. Results: These derivatives were characterized by FT-IR, H-NMR, elemental CHN analysis and then tested for their antimicrobial activity compared to cephalexin against gram-positive, gram-negative bacteria and Candida albicans fungi. Conclusion: The two compounds showed better activity against Staphylococcus aureus, compound 3b is more active against Escherichia coli, and compound 3a is more active against Klebsiella pneumonia.Keywords: Isatin, Bromoisatin, Cephalexin, Schiff base, Antimicrobial activity.